Transnational education for regional economic development? Understanding Malaysia's and Singapore's strategic coupling in global higher education - Marc Philipp Schulze; Jana Maria Kleibert (International Journal of Training and Development, 2021)
Fostering innovation and upskilling labour pools have become key goals in national economic development plans and education and training system reforms since the mid-1990s. For their transformation into knowledge-based economies, countries in Southeast Asia have relied on importing transnational higher education providers and have envisioned themselves as international education hubs. As existing research from transnational education and higher education governance studies as well as economic geography and regional studies has not sufficiently addressed this nexus of transnational education and regional economic development, this paper investigates the role of foreign higher education institutions in economic development strategies in Malaysia and Singapore. It explores why and how states have strategically coupled their higher education systems with transnational education. The comparative case analysis draws on empirical evidence from 42 semi-structured interviews. It finds that despite the two states' ostensibly similar ambitions to attract foreign higher education institutions, policies and outcomes differ strongly. Whereas in Malaysia a structural coupling led foreign subsidiaries to provide foreign degrees to domestic students and generate revenue in the private higher education sector, in Singapore foreign subsidiaries have been deployed strategically to upgrade the talent pool and public higher education system of the city-state via functional coupling. Conceptualizing transnational education policies as forms of strategic coupling contributes to understanding their embeddedness within states' broader, historically formed economic development strategies.
Keywords: 330